2006
DOI: 10.1007/s11746-006-1017-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fractionated Soy Proteins Produced by a New Simplified Procedure

Abstract: It was possible to fractionate soy protein into two soy protein isolate fractions (>90% protein) enriched in either glycinin or b-conglycinin by using a new simplified procedure (referred to as the Deak procedure) employing CaCl 2 and NaHSO 3 . The Deak procedure produced fractions with higher yields of solids, protein, and isoflavones, and similar protein purities as well as improved functional properties compared to fractions recovered by established, more complex soy protein fractionation procedures. The De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 18 publications
8
43
2
Order By: Relevance
“…In contrast to adzuki, functional properties including solubility, emulsifying, foaming and gelling properties of soy protein isolates (Sorgentini et al 1995;Yan et al 2012;Deak et al 2007;Hou and Zhao 2011) and pea protein isolates (Karaca et al 2011;Aluko et al 2009;Barac et al 2010;Boye et al 2010a, b;Adebiyi and Aluko 2011;Taherian et al 2011) are well documented. However, opposite results were obtained concerning functional properties of soy and pea protein isolates.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast to adzuki, functional properties including solubility, emulsifying, foaming and gelling properties of soy protein isolates (Sorgentini et al 1995;Yan et al 2012;Deak et al 2007;Hou and Zhao 2011) and pea protein isolates (Karaca et al 2011;Aluko et al 2009;Barac et al 2010;Boye et al 2010a, b;Adebiyi and Aluko 2011;Taherian et al 2011) are well documented. However, opposite results were obtained concerning functional properties of soy and pea protein isolates.…”
Section: Introductionmentioning
confidence: 95%
“…We prepared fractionated soy protein using a new simplified procedure developed in our lab and known as the Deak procedure [13]. About 100 g of defatted soy flour was extracted with de-ionized water at 15:1 water-to-flour ratio, the pH was adjusted to 8.5 with 2N NaOH, and the resulting slurry was stirred for 1 h. After centrifuging at 14,300·g and 15°C for 30 min, the protein extract (1st protein extract) was decanted and the amount of insoluble fiber residue was determined and sampled for proximate composition.…”
Section: Preparation Of Fractionated Soy Protein By Using a New Simplmentioning
confidence: 99%
“…In previous studies we developed a new soy protein fractionation procedure [24] and reported compositional and functional characteristics of the fractions obtained for IA2020 soy flour [13] and HS/LS soy flour [14]. The procedure was based on differences in calcium binding to glycinin and b-conglycinin in the presence of a reducing agent.…”
Section: Phytic Acid Partitioning In Soy Protein Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…The percent composition of the total storage protein in a given fraction, the purity of the fraction and the composition of a particular subunit of a protein were calculated according to Deak et al [15].…”
Section: Electrophoresismentioning
confidence: 99%